Analysis Student Motivation and Learning Outcomes by Apllying Problem Based Learning and Discovery Learning Models - Freddy Tua Musa Panggabean; Pasar Maulim Silitonga; Jamalum Purba; Jasmidi Jasmidi; Rica Ariani Purba (Universitas Negeri Medan, 2023)
Problem Based Learning and Discovery Learning are models that can increase motivation and learning outcomes of Macromedia Flash-based students on chemical equilibrium materials. The instruments used in this study are test instruments with a cognitive level of C3-C5 and non-test instruments of learning motivation questionnaires. This study aims to: 1) To determine the differences in learning outcomes with the PBL and DL models; and 2) To find a linear and significant relationship between motivatIon and student learning outcomes. The sample was 64 students of class XI MIPA 1 and MIPA 2 who were taken using random sampling techniques. Data analysis using a two-party t-test and a correlation test. The results: 1) There were differences in chemistry learning outcomes of students who were using the PBL and DL models. Where student learning outcomes obtained PBL model (18,219±2,268) and student learning outcomes using the DL model (16,438±2,327) with tvalue (3,101) > ttable (2.00) and a sig value (0.003)< sig(0.05). 2) There is a linear and significant correlation between motivation and student learning outcomes where in the PBL model obtained r count (0.773) > r table (0.349) and dl model obtained rcount (0.770) > r table (0.349) with sig(0.000) value < sig (0.05).